Media ethics : issues and cases - Patterson, Philip; Wilkins, Lee; Painter, Chad, 1977- (Lanham, Maryland : Rowman & Littlefield, an imprint of The Rowman & Littlefield Publishing Group, Inc., 2022)
"The tenth edition of Media Ethics: Issues and Cases has been updated with the most pressing media issues of the past two year, including coverage of the 2020 pandemic and election. This authoritative case book gives students the tools to make ethical decisions in an increasingly complex environment"--
An introduction to ethical decision making -- Information ethics : a profession seeks the truth -- Strategic communication: does client advocate mean consumer adversary? -- Loyalty : choosing between competing allegiances -- Privacy : looking for solitude in the global village -- Mass media in a democratic society : keeping a promise -- Media economics : the deadline meets the bottom line -- Picture this : the ethics of photo and video journalism -- Informing a just society -- The ethical dimensions of art and entertainment -- Becoming a moral adult.
Previous edition was published by Rawman & Littlefield, night edition.
Includes bibliographical references (pages 363-382) and index.
Keywords: Mass media -- Moral and ethical aspects; Communication -- Moral and ethical aspects